: c) 3m+n=9
2m-5n=-11
n = 9-3m
2m-5n = -11
2m-5(9-3m) = -11
2m-45 +15m=-11
17m=34
m=2, n=3
3a+7b=1,5
4a-2=b
3a +7(4a-2) =1,5
3a+28a-14=1,5
31a = 15,5
a=1/2 , b=0
e) 5x=4-2y
4x+y=3
5x+2y=4
y=3-4x
5x+2(3-4x)=4
5x+6-8x=4
-3x=-2
x=2/3, y=1/3
6x-3y=9
x+5y=-9,5
x=-9,5-5y
6(-9,5-5y)-3y=9
-57-30y-3y=9
-33y=66
y=-2, x=0,5
3m+n=9
{n=9-3m
{2m-5(9-3m)=-11
{2m-45+15m=-11
{17m=34
{m=2
{n=9-3·2=3
{n=3
d)4a-2=b
{b=4a-2
{3a+7(4a-2)=1,5
{3a+28a-14=1,5
{31a=15,5
{a=½
{b=4·½-2=0
{b=0
e)
5x=4-2y
{5x+2y=4
{y=3-4x
{5x+2(3-4x)=4
{5x+6-8x=4
{-3x=-2
{x=⅔
{y=3-4·⅔=3-2⅔=⅓
{y=⅓
f)6x-3y=9
{6x-3y=9
{x=-9,5-5y
{6(-9,5-5y)-3y=9
{-57-30-3y=9
{-33y=66
{y=-2
{x=-9,5-5·(-2)=-9,5+10=½
{x=½
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
: c) 3m+n=9
2m-5n=-11
n = 9-3m
2m-5n = -11
2m-5(9-3m) = -11
2m-45 +15m=-11
17m=34
m=2, n=3
3a+7b=1,5
4a-2=b
3a +7(4a-2) =1,5
3a+28a-14=1,5
31a = 15,5
a=1/2 , b=0
e) 5x=4-2y
4x+y=3
5x+2y=4
y=3-4x
5x+2(3-4x)=4
5x+6-8x=4
-3x=-2
x=2/3, y=1/3
6x-3y=9
x+5y=-9,5
6x-3y=9
x=-9,5-5y
6(-9,5-5y)-3y=9
-57-30y-3y=9
-33y=66
y=-2, x=0,5
3m+n=9
2m-5n=-11
{n=9-3m
{2m-5(9-3m)=-11
{n=9-3m
{2m-45+15m=-11
{n=9-3m
{17m=34
{n=9-3m
{m=2
{n=9-3·2=3
{m=2
{n=3
d)4a-2=b
3a+7b=1,5
{b=4a-2
{3a+7(4a-2)=1,5
{b=4a-2
{3a+28a-14=1,5
{b=4a-2
{31a=15,5
{b=4a-2
{a=½
{b=4·½-2=0
{a=½
{b=0
e)
5x=4-2y
4x+y=3
{5x+2y=4
{y=3-4x
{5x+2(3-4x)=4
{y=3-4x
{5x+6-8x=4
{y=3-4x
{-3x=-2
{y=3-4x
{x=⅔
{y=3-4·⅔=3-2⅔=⅓
{x=⅔
{y=⅓
f)6x-3y=9
x+5y=-9,5
{6x-3y=9
{x=-9,5-5y
{6(-9,5-5y)-3y=9
{x=-9,5-5y
{-57-30-3y=9
{x=-9,5-5y
{-33y=66
{x=-9,5-5y
{y=-2
{x=-9,5-5·(-2)=-9,5+10=½
{y=-2
{x=½